2016
DOI: 10.18520/cs/v111/i7/1252-1258
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex-PCR Assay for Detection of some Major Virulence Genes of <i>Salmonella enterica</i> Serovars from Diverse Sources

Abstract: Electrical resistivity imaging technique to delineate coal seam barrier thickness and demarcate water filled voids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
2
9
0
2
Order By: Relevance
“…This data agreed with previous report regarding invA gene in salmonella isolates from pigeons, as it detected in 100% of the examined isolates [47,[59][60]. Detection of fimH and stn gene by 100% in all examined Salmonella isolates from pigeon agreed with that detected by As and Shalaby [47] and Choudhury et al [61], respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This data agreed with previous report regarding invA gene in salmonella isolates from pigeons, as it detected in 100% of the examined isolates [47,[59][60]. Detection of fimH and stn gene by 100% in all examined Salmonella isolates from pigeon agreed with that detected by As and Shalaby [47] and Choudhury et al [61], respectively.…”
Section: Discussionsupporting
confidence: 92%
“…These data totally agreed with previous reports by As and Shalaby [47] and Mezal et al [60] who documented presence of pefA gene in all S. Typhimurium isolated from pigeon. Also, agree for some extent with Ahmed et al [28] and Choudhury et al [61] who found sopE1 and pefA genes with 41.18% and 32.90%, respectively in salmonella isolates. Also, agreed with that previously reported by Dione et al [62] who detected pefA in 40% of the examined Salmonella isolates and they showed correlation between the presence of pefA and Salmonella virulence and resistant to commonly used antimicrobial agents which was similar to our findings in which S. Typhimurium isolate possess pefA gene and resist to rifampicin, erythromycin, ampicillin, gentamycin, chloramphenicol and ceftriaxone 51 used.…”
Section: Discussionsupporting
confidence: 91%
“…These genes are clustered within Salmonella pathogenicity islands (SPIs)-1 and − 21 (SPI-1 to SPI-21) and participate in the adhesion and invasion of the pathogen to the host as inv gene or help in the pathogen survival within the host like mgtC5 gene [6]. Serovars like S. Typhimurium also harbor self-transmissible virulence plasmid-encoded fimbriae ( pef ) fimbrial operon [7]. The enterotoxin ( stn ) gene was demonstrated as a suitable PCR target for detection of Salmonella strains [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Salmonella, neither virulence factor nor toxin gene specific for all serovars have been reported [17,18], and thus the search for a genus specific DNA sequence is more complicated. Even though the recent nomenclature based on DNA homology has classified all the 2500 serovars of Salmonella known so far [4,5] into two species, S. enterica and S. bongori [19][20][21], the data available is insufficient to establish a specific gene or nucleotide sequence that is universal in the Salmonella genus. Only the invA gene has been described as essential for the invasion into epithelial cells by Salmonella.…”
Section: Screening Of Pcr Primers To Test Their Specificitymentioning
confidence: 99%
“…Salmonella spp. contamination occurs through the consumption of contaminated foods including fish and fishery products, and the infection can also be transferred through open as well as tap water [2,3].Salmonella, the Gramnegative bacillus of family Enterobacteriaceae, is widely distributed in nature and can cause diseases ranging from gastroenteritis to typhoid fever [4].More than 2500 serovars of Salmonella are known so far [4,5], and most of them are considered pathogenic to animals and humans [6].Therefore, USFDA has strict guidelines that the seafood products entering the US market should be have zero Salmonella contamination. Similar guidelines have also been laid down in the European Union Directive (94/65/EC) [7].…”
Section: Introductionmentioning
confidence: 99%